The Use Of The Drill Method To Improve The Ability Of Lower Passing In Volleyball Game Students Of SD Negeri 15 Bengkulu Tengah - Riski Suryani; Sumantri, Ajis; Martiani, Martiani (Journal of Physical Education and Sports, 2025)
This study aims to determine the extent to which the drill method can improve the underhand passing technique of fifth grade students of Elementary School 15 Bengkulu Tengah. This study uses a quantitative approach with data collection in the form of numbers that are analyzed statistically. The population in this study were 10 fifth grade students of Elementary School 15 Bengkulu Tengah with a partial sampling technique. The instrument used was the underhand passing test. The results of this study can be concluded that the drill method can improve the learning outcomes of volleyball underhand passing skills of fifth grade students of Elementary School 15 Bengkulu Tengah. This is evidenced by the increase in the average student score from cycle I of 73.93 (quite competent) to 81.07 (competent) in cycle II. Classical completion also increased from 50% in cycle I to 80% in cycle II. Conclusion That the drill method improves the ability of underhand passing techniques of grade V students of SD Negeri 15 Bengkulu Tengah.